2007
DOI: 10.1007/s11663-006-9004-3
|View full text |Cite
|
Sign up to set email alerts
|

A New Lance Design for BOF Steelmaking

Abstract: This article summarizes the outcome of research work carried out to improve the performance of the oxygen lance in the LD steelmaking process. It is stated that the lack of control of the foamy slag and the augmentation of interfacial area creation between the slag and metal are the major hindrances in running the process effectively for improved turn-down steel quality. The ineffectiveness of the existing design in producing liquid metal droplets in the presence of slag foam is explained. In order to augment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…40,44) These studies explored the fundamental behavior of the supersonic jets and greatly helped in propagating the knowledge on oxygen lance performance and its design. R. Sambasivam et al 132) designed a new oxygen lance with a central subsonic nozzle as described in Fig. 5.…”
Section: Supersonic Oxygen Flow Behaviormentioning
confidence: 99%
“…40,44) These studies explored the fundamental behavior of the supersonic jets and greatly helped in propagating the knowledge on oxygen lance performance and its design. R. Sambasivam et al 132) designed a new oxygen lance with a central subsonic nozzle as described in Fig. 5.…”
Section: Supersonic Oxygen Flow Behaviormentioning
confidence: 99%
“…It is known that the Wilcox model predicts free shear flow spreading rates that are in close agreement with measurements for far wakes, mixing layers, plane, round, and radial jets, and is thus applicable to wallbounded flows and free shear flows. On the other hand, the theory of k-e models is widely applied in the models [6][7][8][9][10][11] so far and the realizable one 15) among them can predict the spreading rate of the single jet accurately. Hence, it is wise to compare these two different turbulent models so that more accurate results can be shown considering the multiple-jets coalescence pattern.…”
Section: Turbulence Modelmentioning
confidence: 99%
“…As a result, there have been some efforts [6][7][8][9][10][11] in the field of computational fluid dynamics with the purpose of developing accurate and efficient numerical models to solve the jets flow in the commercial converter. Hatta et al 6) and Peng et al 7) both derived the system of mathematical equations to simulate the steady, quasi-one-dimensional supersonic flow through a single De Laval nozzle, which can be applied to the establishment of the conditions of optimum nozzles of performance.…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Liu et al [ 10 , 11 ] reported that the oxygen preheating technology could significantly improve the initial velocity of the supersonic jet, resulting in a more considerable impaction ability. Sambasivam and Feng et al [ 12 , 13 ] proposed a new arrangement for the oxygen nozzles, proved that an added center nozzle could increase the impaction cavity of the molten bath, and demonstrated the flow field of the oxygen multi-jets. Wang et al [ 14 ] investigated the behavior of supersonic multi-jets generated by an oxygen lance designed with three large-flow-rate Laval nozzles and three small-flow-rate Laval nozzles.…”
Section: Introductionmentioning
confidence: 99%